Does technological support influence the on-the job training (OJT) / Farahiyah Akmal Mat Nawi, Abdul Malek A.Tambi and Hatinah Abu Bakar - Mat Nawi, Farahiyah Akmal; A.Tambi, Abdul Malek; Abu Bakar, Hatinah (Universiti Teknologi MARA Kelantan, 2019)
This paper aimed to analyse the significant influence of technological support to on-the-job training (OJT) in 9 Technical and Vocational Training (TVET) institutions. This is parallel with the Government efforts in enhancing the higher education image in Malaysia. The reasons of this effort is to enhance the academician’s quality as a part of nurturing process to the organization in striving towards its objectives. Empowering education and maintaining the sustainability of the human capital is one of the Government initiatives in supporting the quality of higher education in Malaysia. The reason nurturing the human quality aspect is to help in enhancing the TVET lecturers’ capabilities to help the institution in striving towards its direction. For this reason, the Human Capital Theory and the Technology Acceptance Model (TAM) was adapted to underpin this study in analysing the influence of variables. The study was conducted in 9 polytechnic campuses in East Coast Malaysia consists of three states which are Kelantan, Pahang and Terengganu. The numbers of population (N=1408 respondents) are consists of the lecturers from various departments in the targeted institutions and the sample size (n) contributes 345 respondents from the populations. The questionnaire with 17 questions and 7 points were distributed to gather the feedback from the respondents by using the stratified sampling procedure. For the purpose of assessing the relationship among the variables the Multiple Regression analysis was implemented. The Statistical Package for Social Science (SPSS) output showed there is a strong relationship between all the measured variables. The multiple regression analysis for technological support and on-the-job training shows the significant value = 0.000 with B=0.610, t=14.25